Karanie z mocy ustawy o przeciwdziałaniu narkomanii z perspektywy wybranych teorii kary - Jakub Sukiennik (Alcoholism and Drug Addiction, 2015)
Increasing amount of legislation is being passed to regulate economic and social relations. It seems that in certain areas, its implementation can be logically justified. However, in the case of increasing criminalisation of drug-related activities that occurred during the Transformation of 1989, this leads to excessive paternalism and raises problems of interpretation. The object of this study will be drug prohibition designed to protect public health. This institution restricts freedom, especially personal liberty in the sense of personal rights and of the right to dispose of economic assets. Consumption of these substances generates negative externalities, whose formation is an argument in favour of state intervention. The aims of this article are to answer whether prohibition as a method of regulating the drug market, adopted in the 90's, seems to be effective and socially desirable from the point of view of utilitarian, retributive and abolitionist theories of punishment.